ORGANIZATIONAL AND PEDAGOGICAL CHARACTERISTICS OF PRESCHOOL EDUCATION SYSTEM ABROAD - Toshmatova Zamira Jumanovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article contains information about didactics of the preschool education system, organizational and pedagogical features of the preschool education system in foreign countries.